Kreativität und Reproduktion. Annäherung an den Bildungshorizont von Ursula Weida - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs. Forschungsberichte – Projektangebote – Forschungskontexte)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Die Artes liberales im frühen Mittelalter (5.-9. Jh.). Das Quadrivium und der Komputus als Indikatoren für Kontinuität und Erneuerung der exakten Wissenschaften zwischen Antike und Mittelalter - Englisch, Brigitte

Problem Independent Distributed Simulated Annealing and its Applications - Diekmann, Ralf; Simon, Jens (Applied Simulated Annealing)

Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk

Stanislaw Przybyszewski: Schnee und andere Dramen (Edition) - Eke, Norbert Otto

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 7. Aufzeichnungen. Vermischte Schriften. Text und Kommentar (Edition) - Eke, Norbert Otto; Oellers, Norbert; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Rettung des Sinns. Jaákobs Traum und das Projekt einer Geschichtstheodizee - Eke, Norbert Otto (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

Richard Beer-Hofmann – Zur Einführung - Eke, Norbert Otto; Helmes, Günter (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

„Freiheit ist nur in dem Reich der Träume“. Revolutionsprojektionen deutscher Dramen nach 1789. Ein historischer Aufriß (mit einem Ausblick bis zum Nachmärz) - Eke, Norbert Otto (Grabbe Jahrbuch 12)

Eine Gesamtbibliographie des deutschen Romans 1815-1830. Anmerkungen zum Problemfeld von Bibliographie und Historiographie - Eke, Norbert Otto (Zeitschrift für Germanistik)

„Deutschland ortlos“. Dekonstruktionen des Nationalen bei Heiner Müller - Eke, Norbert Otto (Dichter und ihre Nation)

Continuous Mixture Densities and Linear Discriminant Analysis for Improved Context-Dependent Acoustic Models - Aubert, Xavier L.; Haeb-Umbach, Reinhold; Ney, Hermann (ICASSP, Minneapolis)
Linear discriminant analysis (LDA) experiments reported previously (ICASSP-92 vol.1, p.13-16), are extended to context-dependent models and speaker-independent large vocabulary continuous speech recognition. Two variants of using mixture densities are compared: state-specific modeling and the monophone-tying approach where densities are shared across the states relevant to the same phoneme. Results are presented on the DARPA Resource Management (RM) task for both speaker-dependent (SD) and speaker-independent (SI) parts. Using triphone models based on LDA and continuous mixture densities, significant improvements have been observed and the following word error rates have been achieved: for the SD part, 7.8% without grammar and 1.5% with word pair; and for the SI part, 17.2% and 4.6%, respectively. These scores are averaged over 1200 SD or SI evaluation sentences and are among the best published so far on the RM database.

The Philips Research System for Large-Vocabulary Continuous-Speech Recognition - Steinbiss, Volker; Ney, Hermann; Haeb-Umbach, Reinhold; Train, B.-H.; Essen, U.; Kneser, Reinhard; Oerder, Martin; Meier, H. G.; Aubert, X.; Dugast, Christian; Geller, Dieter; Hoellerbauer, W.; et al. (EUROSPEECH, Berlin)
This paper gives a status report of the Philips research system for phoneme-based, large-vocabulary, continuous-speech recognition. Like for many other systems, the recognition architecture is based on an integrated statistical approach. We describe the characteristic features of the system as opposed to other systems: 1. The Viterbi criterion is consistently applied both in training and testing. 2. Continuous mixture densities are used without tying or smoothing. 3. Time-synchronous beam search in connection with a phoneme look-ahead is applied to a tree-organized lexicon. The system has been successfully applied to the American English DARPA RM task. Here, we report experimental results for a German 13 000-word Philips internal dictation task. In addition to the scientific prototype, a PC version has been set up which is described here for the first time.

Chemisorption of aluminium on GaAs(110) - Schmidt, Wolf Gero; Srivastava, G P (Journal of Physics: Condensed Matter)

́Augen wie Leuchtkäfer ́ - Zur Sprache der Liebe in Mario Vargas Llosas ́ Lob der Stiefmutter - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 37. Mai 1993: Sprachen der Liebe)

Loser und fester Anschluß. Versuch der Neubewertung einer abgelegten Kategorie - Maas, Utz; Tophinke, Doris (Sprachwandel und Sprachgeschichte. FS für Helmut Lüdtke)

Sprachentwicklung in Geschichte und Gegenwart - Maas, Utz; Frankenbusch, Marita; Johannlückens, Ralf; Stöwer-Gaus, Ursula; Striezel, Marion; Tophinke, Doris (Damme. Eine Stadt in ihrer Geschichte)

Christi Himmelfahrt. Predigttext: 1. Könige 8,22-24.26-28 - Schroeter-Wittke, Harald (Gottesdienstpraxis. Serie A. III. Perikopenreihe Band 2)

12. März - Geburtstag von Paul Gerhardt (1607-1676) - Schroeter-Wittke, Harald (Woran sie glaubten - wofür sie lebten. 365 Wegbegleiter für die Tages des Jahres)

Walter Benjamin und Bertolt Brecht - Ansätze zu einer dialektischen Ästhetik in den dreißiger Jahren. - Müller, Inez